Manajemen perpustakaan sekolah - mreza rokan (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2017)
In the world of education, the library is an information place that serves as a learning resource or learning laboratory that allows educators and educators improve their quality. But the most important thing in optimizing the function of the library is the reading interest that must be owned by someone and also the library management that can increase reading interest.Keywords: Library leadership, school library